Reconstructing Prabowo Subianto's Image in TikTok Content @partaigerindra: A Framing Analysis of the 2024 Presidential Election Campaign - Safitri, Sarere; Sugiantoro, Hari Akbar (Jogjakarta Communication Conference (JCC), 2025)
The development of social media has transformed political communication strategies, especially in election campaigns. TikTok has become one of the main platforms used to build political image through short video-based content. This research aims to analyze how framing in TikTok content of @partaigerindra account is used to reconstruct Prabowo Subianto's image during the 2024 presidential election campaign. By using descriptive qualitative method and Entman's framing analysis (1993), this study identifies the political communication patterns applied in shaping Prabowo's image. The results showed that the @partaigerindra account actively used framing strategies to change public perception of Prabowo Subianto, from a figure synonymous with the military to a figure that is more humorous and closer to the public, especially generation Z voters. The narrative built through TikTok content emphasized aspects of humor, closeness, and engagement in digital trends favored by Generation Z. In addition, TikTok's for You Page (FYP) algorithm plays a role in massively disseminating this content, increasing audience engagement, and strengthening Prabowo's positive image among young voters. This research provides insights into how social media can be used to reconstruct Prabowo Subianto's image during the 2024 elections and can be a reference for academics and digital campaign practitioners in understanding political framing strategies in the digital era.